2015
DOI: 10.1371/journal.pntd.0003980
|View full text |Cite
|
Sign up to set email alerts
|

Taenia solium: Development of an Experimental Model of Porcine Neurocysticercosis

Abstract: Human neurocysticercosis (NC) is caused by the establishment of Taenia solium larvae in the central nervous system. NC is a severe disease still affecting the population in developing countries of Latin America, Asia, and Africa. While great improvements have been made on NC diagnosis, treatment, and prevention, the management of patients affected by extraparenchymal parasites remains a challenge. The development of a T. solium NC experimental model in pigs that will allow the evaluation of new therapeutic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Most of our understanding about immunopathogenesis of cysticercosis is based on the mice or rat models, which cannot be extrapolated to human beings. A series of studies with T. solium have established that the course of infection and its histopathology and the response shown against antiparasitic treatment in swine is similar to the one in humans . However, a major drawback of this model is that being a large animal, the handling of pig is costly and requires a dedicated facility with skilled workforce.…”
Section: Animal Models For Neurocysticercosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of our understanding about immunopathogenesis of cysticercosis is based on the mice or rat models, which cannot be extrapolated to human beings. A series of studies with T. solium have established that the course of infection and its histopathology and the response shown against antiparasitic treatment in swine is similar to the one in humans . However, a major drawback of this model is that being a large animal, the handling of pig is costly and requires a dedicated facility with skilled workforce.…”
Section: Animal Models For Neurocysticercosismentioning
confidence: 99%
“…Recently, Fleury et al., (2105) published a surgical method to directly infect the pig brain to develop an NCC model. In this method, eggs collected from human T. solium carriers were hatched in vitro using 0.75% sodium hypochlorite in water.…”
Section: Animal Models For Neurocysticercosismentioning
confidence: 99%
“…Epidemiologic studies have demonstrated tight clustering household or household contacts with NCC patients have three times higher risk having positive serology for cysticercosis compared with controls 5 . NCC is a common cause of neurological disease transmitted through parasites called Taenia solium (T. solium) 6 . It is endemic in Africa, Asia and Latin America, making it the major cause of epilepsy and Bangladesh J Infect Dis 25 June 2016│ Volume 3│Number 1 convulsion in these regions 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the infected animals presented with tissue alterations and lesions such as encephalitis, perivasculitis, ventriculomegaly, ependymitis, meningitis, microgliosis accompanied by the parasite's death, and extraparenchymal and parenchymal inflammatory infiltration 6,18 . Other experimental models have been proposed but instead of using T. crassiceps cysticerci they performed an intracranial inoculation of T. solium oncospheres in rats 19 and in swine 20 . The rat NCC model reported that the infected animals presented with epilepsy, inflammatory infiltration, perivascular infiltrate, angiogeneses, spongy changes and mass effect in the brain tissue 19 .…”
mentioning
confidence: 99%
“…The rat NCC model reported that the infected animals presented with epilepsy, inflammatory infiltration, perivascular infiltrate, angiogeneses, spongy changes and mass effect in the brain tissue 19 . In the swine NCC model, after four months of infection, it was possible to observe calcified cysticerci surrounded by an exacerbated inflammatory response with lymphocyte infiltration and increased inflammatory markers 20 . The BALB/c mice are genetically susceptible to intraperitoneal infection with T. crassiceps cysticerci because they present a Th2 immune profile 7,9 .…”
mentioning
confidence: 99%